Business statistics in practice - Bowerman, Bruce L. (The Mcgraw-Hill/Irwin series in operations and decision sciences, 2014)
Business Statistics in Practice, Seventh Edition provides a modern, practical and unique framework for teaching an introductory course in Business Statistics. The textbook employs realistic examples, continuing case studies and a business improvement theme to teach the material. The Seventh Edition features more concise and lucid explanations, an improved topic flow and a sensible use of the best and most compelling examples.